Complete Genome Analysis of Thermus parvatiensis and Comparative Genomics of Thermus spp. Provide Insights into Genetic Variability and Evolution of Natural Competence as Strategic Survival Attributes - Tripathi, Charu; Mishra, Harshita; Khurana, Himani; Dwivedi, Vatsala; Kamra, Komal; Negi, Ram K.; Lal, Rup (Frontiers in Microbiology, 2017)
Thermophilic environments represent an interesting niche. Among thermophiles, the genus Thermus is among the most studied genera. In this study, we have sequenced the genome of Thermus parvatiensis strain RL, a thermophile isolated from Himalayan hot water springs (temperature > 96 °C) using PacBio RSII SMRT technique. The small genome (size 2.01 Mbp) comprises a chromosome (1.87 Mbp) and a plasmid (143 Kbp), designated in this study as pTP143. Annotation revealed a high number of repair genes, a squeezed genome but containing highly plastic plasmid with transposases, integrases, mobile elements and hypothetical proteins (44%). We performed a comparative genomic study of the group Thermus with an aim of analysing the phylogenetic relatedness as well as niche specific attributes prevalent among the group. We compared the reference genome RL with 16 Thermus genomes to assess their phylogenetic relationships based on 16S rRNA gene sequences, average nucleotide identity, conserved marker genes (31 and 400), pan genome and tetranucleotide frequency. The core genome of the analysed genomes contained 1177 core genes and many singleton genes were detected in individual genomes, reflecting a conserved core but adaptive pan repertoire. We demonstrated the presence of metagenomic islands (chromosome:5, plasmid:5) by recruiting raw metagenomic data (from the same niche) against the genomic replicons of T. parvatiensis. We also dissected the CRISPR loci wide all genomes and found widespread presence of this system across Thermus genomes. Additionally, we performed a comparative analysis of competence loci wide Thermus genomes and found evidence for recent horizontal acquisition of the locus and continued dispersal among members reflecting that natural competence is a beneficial survival trait among Thermus members and its acquisition depicts unending evolution in order to accomplish optimal fitness.